Fabrication of injectable CuS nanocomposite hydrogels based on UCST-type polysaccharides for NIR-triggered chemo-photothermal therapy. Issue 98 (20th November 2018) - Zheng, Yueyuan; Liang, Yuqing; Zhang, Depan; Zhou, Zhijun; Li, Juan; Sun, Xiaoyi; Liu, You-Nian
Abstract : Nanocomposite hydrogels were readily prepared via a one-pot method with a high NIR-thermal conversion efficiency (54.6%). Abstract : Injectable nanocomposite hydrogels containing small copper sulfide nanoparticles (6–8 nm) with a 54.6% photothermal conversion efficiency have been facilely prepared by applying an upper critical solution temperature (UCST)-type biopolymer gellan. This minimally invasive formulation ablates cancer completely in vivo after NIR-triggered chemo-photothermal therapy.